Level of elderly-supportive infrastructure, fine particulate matter and cardiovascular disease hospitalisations: a time-stratified case-crossover study in Wuhan - Mengxue Qin; Xingyuan Liu; Luyao Wang; Tengchong Huang; Xiuran Zuo; Yuliang Zou (Global Health Action)
Background Amid rapid urbanisation, the health effects of the built-environment have been widely studied, while research on elderly-supportive infrastructure and its interaction with PM2.5 (PM, Particulate Matter) exposure remains limited. Objectives To examine the effect of PM2.5 on cardiovascular hospitalisation risk among the elderly and the moderating role of elderly-supportive infrastructure in Wuhan, a city undergoing rapid urbanisation. Methods A time-stratified case-crossover design was adopted in which the K-means cluster analysis was applied to categorize elderly-supportive infrastructure. The correlation of PM2.5 with cardiovascular hospitalisations and the moderating role of elderly-supportive infrastructure were elucidated through the conditional logistic regression and z-test. Nonlinear relationships among variables were determined using restricted cubic splines. Results 173,486 case days and 589,188 control days were included. The cumulative lag effect of PM2.5 increased over time, peaking at 5 days. For every 10 µg/m3 increase in PM2.5, the risk of hospitalisation rose by 1.5% (OR = 1.0150, 95% CI: 1.0113–1.0190). The aforementioned effect of PM2.5 exposure on health did not differ among varying levels of elderly-supportive infrastructure within a 300 m buffer zone. When the buffer zone was extended to 500 and 1000 m, a higher level of elderly-supportive infrastructure mitigated the adverse effects of short-term PM2.5 exposure on cardiovascular hospitalisations (p = 0.013), particularly for stroke (p = 0.017) and ischaemic heart disease (p = 0.026). Conclusions Our findings suggest that high-level elderly-supportive infrastructure may protect against the adverse effects of PM2.5 on cardiovascular hospitalisation, highlighting the need to optimize elderly-supportive infrastructure for its health benefits in the elderly.